Combining 18F‐FDG PET/CT and Serum Lactate Dehydrogenase for Prognostic Evaluation of Small Cell Lung Cancer - Lin, Xiaoping; Xiao, Zizheng; Hu, Yingying; Zhang, Xu; Fan, Wei (Frontiers in Pharmacology, 2020)
Objective To evaluate the value of using 18F-FDG PET/CT imaging in combination with serum lactate dehydrogenase (LDH) for predicting the prognosis of newly diagnosed small cell lung cancer (SCLC). Methods We reviewed 118 patients with pathologically proven SCLC who underwent 18F-FDG PET/CT imaging evaluation in our hospital. Among these patients, 54 patients were limited disease (LD), and 64 patients were extensive disease (ED). The maximum standardized uptake value (SUVmax) of primary tumor was measured. A Cox proportional hazards model was used to evaluate age, sex, performance status, lactate dehydrogenase (LDH), tumor stage and SUVmax on the prediction of overall survival (OS) and median survival time (MST) of patients. Subgroup analysis was performed based on the SUVmax in combination with LDH. Results According to the ROC curve, the optimal cut-off value of SUVmax was 10.95. The AUC was 0.535 (95% CI: 0.407 ~ 0.663). The patients were divided into four groups according to the SUVmax (cut-off 10.95) and LDH (cut-off 245 U/L). In LD. There was no significant difference in MST among the different groups (p =0.057). In patients with ED, there was no significant difference in MST among the different groups (p =0.742). Among all patients, 27 had low SUVmax and normal LDH, and their MST was 36 months (95% CI, 12.98-59.02); 91 patients had high SUVmax and/or high LDH, and their MST was 20 months (95% CI, 15.47~24.53). The difference between these two groups was significant (p =0.045). In patients with LD, 16 patients had low SUVmax and normal LDH, and their MST was 72 months (95% CI, 26.00 ~118.0); 38 patients had high SUVmax and/or high LDH, and their MST was 27 months (95% CI, 20.80~33.21). The difference between these two groups was significant (p=0.012). Conclusion 18F-FDG PET/CT in combination with serum LDH were prognostic factors of overall survival of SCLC patients. The prognosis of patients with LD SCLC who had low SUVmax of the primary tumor and normal LDH was better than that of patients with high SUVmax and/or high LDH.